Social Capital: A Factor in Region’s Sustainable Development - А. Guzhavina Tatiana; А. Mekhova Albina (European Journal of Sustainable Development, 2018)
The views on sustainable development demonstrate a new trend – a gradual transition from the macro-level to the meso- and micro-level. This interpretation is typical for the so-called cluster approach to sustainable development. The cluster approach is based on the principles of corporate citizenship and is often used to study the formation mechanisms of sustainable development in the region. Within the framework of this approach, non-material social resources that contribute to the region’s competitiveness are of particular importance. The authors believe it would be efficient to explore these resources through the concept of social capital. Modern research shows that social capital is an intangible factor and a resource that affects the economy and social welfare in general. The article presents the author’s view on some conceptual issues underlying the study of social capital. The efficiency of applying the concept of social capital to study the problems of regions’ sustainable development is determined. A number of proposals on empirical investigation of the role and importance of regional social capital of the region are made. Keywords: sustainable development, social capital, region, indicator model